2013
DOI: 10.1210/jc.2013-2142
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous Mutations in Natriuretic Peptide Receptor-B (NPR2) Gene as a Cause of Short Stature in Patients Initially Classified as Idiopathic Short Stature

Abstract: We identified heterozygous NPR2 mutations in 6% of patients initially classified as ISS. Affected patients have mild and variable degrees of short stature without a distinct phenotype. Heterozygous mutations in NPR2 could be an important cause of nonsyndromic familial short stature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 38 publications
6
103
1
3
Order By: Relevance
“…NPR2 variants were absent in our patient group. This is inconsistent with previous studies which identified NPR2 mutations in 1.9-12.7% of ISS cases [21,22]. Since Amano et al identified pathogenic NPR2 mutations only in ~2% of Japanese short stature patients [23], such mutations may be relatively rare in the Japanese population.…”
Section: Phenotypic Characteristics Of Patients With Sequence Variantscontrasting
confidence: 62%
“…NPR2 variants were absent in our patient group. This is inconsistent with previous studies which identified NPR2 mutations in 1.9-12.7% of ISS cases [21,22]. Since Amano et al identified pathogenic NPR2 mutations only in ~2% of Japanese short stature patients [23], such mutations may be relatively rare in the Japanese population.…”
Section: Phenotypic Characteristics Of Patients With Sequence Variantscontrasting
confidence: 62%
“…Homozygous inactivating mutations of NPR2 (encoding the main CNP receptor) cause a severe skeletal dysplasia, acromesomelic dysplasia, Maroteaux type (124). Initial observations that relatives heterozygous for NPR2 mutations of patients with acromesomelic dysplasia are shorter than non-carriers (125), were confirmed by recent studies (126,127,128,129). The phenotype of heterozygous NPR2 mutations is similar to that of patients with SHOX haploinsufficiency (Leri-Weill syndrome), with short forearms and lower legs (mesomelia), except for the absence of Madelung deformity (130).…”
Section: Cnp-npr2 Pathwaymentioning
confidence: 92%
“…In clinical settings for the treatment of impaired skeletal growth, we could use OSTN and CNP for different purposes. Concerning therapeutic application for specific skeletal dysplasias, OSTN therapy, rather than CNP therapy, may be beneficial for the heterozygous NPR2 defects, because they mainly cause short stature with mild skeletal defects in appendicular bones (12,15). Furthermore, heterozygous NPPC defects, which have recently been identified and are associated with skeletal abnormalities similar to those seen with heterozygous NPR2 defects, could also be a good application for OSTN therapy (16).…”
Section: 4mentioning
confidence: 99%
“…In fact, NPR-B and CNP are both expressed in the cartilaginous growth plate, and homozygous loss-of-function mutations of NPR-B not only in murine models (7,8) but also in the human disorder acromesomelic dysplasia type Maroteaux (9,10) cause impaired skeletal growth. In addition, heterozygous loss-offunction mutations of NPR-B have been reported to cause short stature and mild skeletal defects (11)(12)(13)(14)(15), and recently heterozygous loss-of-function mutations of CNP have also been shown to cause similar skeletal defects to those of NPR-B (16). Furthermore, a recent case series showed that gain-of-function mutations in NPR-B cause a skeletal overgrowth phenotype (17,18), demonstrating the ability of CNP/NPR-B signaling to stimulate bone growth in humans.…”
Section: Introductionmentioning
confidence: 99%